No good deed goes unpunished: removing barriers to wildlife conservation on private lands - Danvir, Rick, speaker; Allison, Lesli, moderator; Taggart, Craig, moderator; Danvir, Rick, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Contrary to common perception, many private landowners across the West have a strong conservation ethic and an interest in helping to advance species recovery, including threatened and endangered species. Conservation efforts by private landowners are essential to the management, restoration and preservation of key wildlife movement corridors and habitats across the West. Unfortunately, many landowners fail to realize their desired conservation and economic goals. On occasion, their efforts can best be summed up as "No good deed goes unpunished." State and local agricultural tax policies, inflexible public-lands grazing policies on comingled private-public grazing allotments, inflexible and incompatible forest management practices on public-private land interfaces, lawsuits and appeals from environmental groups, and liability concerns from neighboring landowners are a few of the challenges impeding landowner participation and success in wildlife management and species recovery efforts. Case studies from private ranches in the western U.S. provide examples where county, state and federal policies and perceptions (water, tax, planning and endangered species policies) at times stifle creativity and hinder landowner-initiated efforts to improve management of livestock, rangelands, forests, wildlife and habitat. By reviewing these case studies, we hope to highlight how some policies (such as water laws, grazing and logging-tax requirements) act as barriers or disincentives to voluntary landowner conservation. Our goal is develop policies that facilitate, incentivize and reward voluntary conservation by landowners.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses